Myogenin and MyoD join a family of skeletal muscle genes regulated by electrical activity. - Eftimie, R (1991)
Myogenin and MyoD are proteins that bind to the regulatory regions of a battery of skeletal muscle genes and can activate their transcription during muscle differentiation. We have recently found that both proteins interact with the enhancer of the nicotinic acetylcholine receptor (nAChR) alpha subunit, a gene that is regulated by innervation. This observation prompted us to study if myogenin and MyoD transcript levels are also regulated by skeletal muscle innervation. Using Northern blot analysis, we found that MyoD and myogenin mRNA levels begin to decline at embryonic day 17 and attain adult levels in muscle of newborn and 3-week-old mice, respectively. In contrast, nAChR mRNAs are highest in newborn and 1-week-old mouse muscle and decline thereafter to reach adult levels in 3-week-old mice. To determine if the down-regulation of myogenin and MyoD mRNA levels during development is due to innervation, we quantitated message levels in adult calf muscles after denervation. We found that in denervated muscle myogenin and MyoD mRNAs reach levels that are approximately 40- and 15-fold higher than those found in innervated muscle. Myogenin mRNAs begin to accumulate rapidly between 8 and 16 hr after denervation, and MyoD transcripts levels begin to increase sharply between 16 hr and 1 day after denervation. The increases in myogenin and MyoD mRNA levels precede the rapid accumulation of nAChR alpha-subunit transcripts; receptor mRNAs begin to accumulate significantly after 1 day of denervation. The effects of denervation are specific because skeletal alpha-actin mRNA levels are not affected by denervation. In addition, we found that the repression of myogenin and MyoD expression by innervation is due, at least in part, to "electrical activity." Direct stimulation of soleus muscle with extracellular electrodes repressed the increase of myogenin and MyoD transcripts after denervation by 4- to 3-fold, respectively. In view of these results, it is interesting to speculate that myogenin and/or MyoD may regulate a repertoire of skeletal muscle genes that are down-regulated by electrical activity.